Management of grade V splenic injury with splenic artery embolization in pregnancy: A case report - Kumaressan Ragunathan; Jane Thorn (Elsevier, 2022)
Introduction: Trauma is known to be a causative factor of mortality in pregnancy. However, splenic injuries are atypical in pregnancy. In this case report, we discuss a novel approach using splenic artery embolization to manage a severe form of splenic injury in pregnancy. Case Presentation:: A 35-year-old multigravida presented at 28 weeks of gestation. She had sustained grade V splenic injury and was treated with splenic artery embolization. She continued her pregnancy up to term following the treatment. Discussion: Splenic artery embolization should be considered as an alternative to laparotomy in managing severe forms of splenic injury in pregnancy.